Optimal Executive Compensation versus Managerial Power: A Review of Lucian Bebchuk and Jesse Fried's Pay without Performance: The Unfulfilled Promise of Executive Compensation - Weisbach, Michael S (Journal of Economic Literature, 2007)
This essay reviews Lucian A. Bebchuk and Jesse M. Fried's Pay without Performance: The Unfulfilled Promise of Executive Compensation. Bebchuk and Fried criticize the standard view of executive compensation, in which executives negotiate contracts with shareholders that provide incentives that motivate them to maximize the shareholders' welfare. In contrast, Bebchuk and Fried argue that executive compensation is more consistent with executives who control their own boards and who maximize their own compensation subject to an “outrage constraint.” They provide a host of evidence consistent with this alternative viewpoint. The book can be evaluated from both positive and normative perspectives. From a positive perspective, much of the evidence they present, especially about the camouflage and risk-taking aspects of executive compensation systems, is fairly persuasive. However, from a normative perspective, the book conveys the idea that policy changes can dramatically improve executive compensation systems and consequently overall corporate performance. It is unclear to me how effective potential reforms designed to achieve such changes are likely to be in practice.